IMPLEMENTASI MODEL LEARNING TOGETHER UNTUK MENINGKATKAN KECAKAPAN KEWARGANEGARAAN SISWA DI SMP - Ika Murtiningsih; Kokom Komalasari (Universitas Negeri Malang, 2017)
Abstract: The purposes of this study was to describe and analyze implementation learning together models to improve students' civic skills. Methods used in this research was the qualitative approach with naturalistic inquiry methods. Data collection techniques such as interviews, observation, and documentation. The results showed that implementation learning together models can improve students' civic skills is think critically and participate actively. Students' have the intellectual skills to identifying, describing, explaining, analyzing problems, evaluating, and taking and defending opinion that with grasp of the sovereignty people and system government in Indonesia. Students' also have the participation skills in the interacting, monitoring, and influencing in the group. The improvement from the standpoint of civics education is one of the components that should be embodied in the formation of the smart and good citizenAbstrak: Tujuan dari kajian ini adalah mendeskripsikan implementasi model learning together untuk meningkatkan kemampuan kewarganegaraan siswa. Metode yang digunakan dalam kajian ini adalah pendekatan kualitatif dengan metode inquiry naturalistik. Teknik pengumpulan data seperti wawancara, observasi, dan dokumentasi. Hasil menunjukkan bahwa penerapan pembelajaran bersama model dapat meningkatkan kemampuan berprestasi siswa berpikir kritis dan berpartisipasi aktif. Siswa memiliki kemampuan intelektual untuk mengidentifikasi, menjelaskan, menganalisis masalah, mengevaluasi, dan mengambil serta mepertahankan pendapat tentang pemahaman kedaulatan rakyat dan sistem pemerintahan di Indonesia. Siswa juga memiliki kemampuan partisipasi dalam berinteraksi, memantau, dan mempengaruhi kelompok tersebut. Perbaikan dari sudut pandang pendidikan kewarganegaraan merupakan salah satu komponen yang harus diwujudkan dalam pembentukan warga yang cerdas dan baik DOI : http://dx.doi.org/10.17977/um019v2i22017p098